Elimination of Gender Discriminatory Legal Provision by the Supreme Court of Nepal with Reference to Women’s Right to Property - Subedi, Nutan Chandra (Tribhuvan University Journal, 2010)
Not available. Key words: Gender Discriminatory; Legal Provision; Supreme Court; Women’s Rights; Nepal Tribhuvan University Journal Volume XXVI No. 1, 2009 Page: 37-54